(untitled) (The Review of Diabetic Studies, 2025)
Background: Over 200,000 patients annually in the United States are affected by chronic hematologic malignancies, including chronic myeloid leukemia (CML), chronic lymphocytic leukemia (CLL), multiple myeloma (MM), and non-Hodgkin lymphoma (NHL), with oral targeted therapies like tyrosine kinase inhibitors and immunomodulators transforming therapy. Nonadherence (15-50%) due to regimen complexity, toxicities (AEs), cost, and psychosocial concerns threatens outcomes, increasing relapse and hospitalization risks. Aim: The clinical impact of Pharmacist-Led Oral Chemotherapy Adherence Programs (POCAPs) on adherence, clinical outcome, and implementation problems in chronic hematologic cancers is evaluated by this review. Methods: Narrative review based on PRISMA-ScR guidelines examined 40 studies (2010-2025) from PubMed, Scopus, Web of Science on POCAPs in CML, CLL, MM, NHL. Adherence (MPR/PDC), clinical endpoints (e.g., MMR, PFS), and patient satisfaction were the endpoints. Results: POCAPs improved adherence from 70-85% to 90-99%, CML MMR rates to 85%, and CLL PFS by 18-20%. AEs were reduced (e.g., 30% reduction in grade 3/4 cytopenias in MM), and 95% satisfaction was attained. Financial toxicity and limited rural access were obstacles. Conclusions: POCAPs have an undeniable effect on adherence and outcomes and need to become part of routine care through telehealth, AI, and policy modification.